Indecomposable and isomorphic objects in the category of monomial matrices over a local ring - Bondarenko, V. M.; Bortos, M. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the indecomposability and isomorphism of objects from the category of monomial matrices Mmat(K) over a commutative local principal ideal ring K (whose objects are square monomial matrices and the morphisms from X to Y are the matrices C such that XC = CY). We also study the subcategory Mmat_0(K) of the category Mmat(K) with the same objects and only those morphisms that are monomial matrices.